Analisis Perbandingan Batas Minimal Usia Perkawinan menurut Empat Mazhab - Ikhsan, Alwi; Abd Hadi; Janeko, Janeko (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
Marriage is a sunnatullah that generally applies to all of Allah's creatures, both humans, animals and plants. This research aims to analyze the comparison of minimum marriage age limits according to four schools of thought, using qualitative research methods in the type of literature study. From the research it was found that the Qur'an and hadith do not specifically mention the minimum age limit for marriage. The fuqaha set an age limit as determining the age of puberty. Imam Syafi'i School, Hambali, Hanafi, a child is considered to be mature when he is 15 years old. Meanwhile, the Imam Maliki school of thought also limits the age of 17 years as the age of puberty.